IHRD Implementation Programme : What does a duty of candour mean for Health and Social Care? : Analysis of views from involvement events.: What does a duty of candour mean for Health and Social Care? : Analysis of views from involvement events. ([2020]) - McBride, Peter; (Physician), Donnelly, Patricia; Fordyce, Claire; Weir, Alan
No abstract available